SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY ON EXERCISE TOLERANCE IN HEART FAILURE PATIENTS: TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) PADA TOLERANSI AKTIVITAS PASIEN GAGAL JANTUNG - Azizah Yuni Saputri; Tutiany Tutiany; Tri Riana Lestari (Journal of Health and Cardiovascular Nursing, 2026)
Heart failure causes a decrease in the heart’s ability to pump blood, making patients prone to exercise intolerance. This study was conducted to analyze the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on exercise tolerance in patients with heart failure. SEFT is a method that combines spiritual elements and energy psychology techniques through the application of pressure to 18 body points, consisting of 6 points on the head, 3 points in the chest area, and 9 points in the hand area. This study employed a quasi-experimental design using a pretest-posttest method with a control group. A total of 34 respondents were selected using purposive sampling at a Type B hospital. The sample size was determined based on the formula for hypothesis testing to compare the means of two independent groups, resulting in 17 respondents each for the intervention group and the control group. The respondents included in the study were patients diagnosed with heart failure who were conscious, had limited mobility, and were willing to participate in the study. SEFT was administered over three days, with each session lasting 10–15 minutes. Data analysis was performed using paired t-tests and independent t-tests. The study results indicate that there was a significant increase in exercise tolerance in the group receiving SEFT therapy compared to the control group (p < 0.005). SEFT therapy is believed to produce a relaxing effect, stimulate the release of endorphins, and help balance the body’s energy.